(untitled) (Global Journal of Science Frontier Research, 2020)
In the article questions of the penetration of the electric currents of different frequency into the soil are examined. Is built the electric analogue of the organic cellular structures, which the root system of plants is. The dispersion properties of such structures are explained. The technical realization of experiments on a study of the influence of high-frequency currents in the soil on its fertility is proposed.